2016
DOI: 10.5194/amt-9-3115-2016
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Vaisala radiosondes RS41 and RS92 at the ARM Southern Great Plains site

Abstract: Abstract. In the fall of 2013, the Vaisala RS41 (fourth generation) radiosonde was introduced as a replacement for the RS92-SGP radiosonde with improvements in measurement accuracy of profiles of atmospheric temperature, humidity, and pressure. In order to help characterize these improvements, an intercomparison campaign was undertaken at the US Department of Energy's Atmospheric Radiation Measurement (ARM) Climate Research Facility site in northcentral Oklahoma, USA. During 3-8 June 2014, a total of 20 twin-r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
88
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(100 citation statements)
references
References 47 publications
10
88
2
Order By: Relevance
“…For a measurement network like GRUAN, it is essential to have more than one good-quality radiosonde type for operations. Instrument biases are also influenced by clouds as shown in Jensen et al (2016) who found systematic differences in temperature measurements greater than 2 K between the Vaisala RS92 and RS41 radiosonde when exiting cloud layers. This large difference in temperature measurements between the two radiosondes was attributed to the wetbulb effect, in which the temperature sensor gets wet while passing through a cloud layer and is subject to evaporative cooling after entering drier parts of the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a measurement network like GRUAN, it is essential to have more than one good-quality radiosonde type for operations. Instrument biases are also influenced by clouds as shown in Jensen et al (2016) who found systematic differences in temperature measurements greater than 2 K between the Vaisala RS92 and RS41 radiosonde when exiting cloud layers. This large difference in temperature measurements between the two radiosondes was attributed to the wetbulb effect, in which the temperature sensor gets wet while passing through a cloud layer and is subject to evaporative cooling after entering drier parts of the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, inter-comparisons of measurements from dual or quadruple (two of each instrument type) radiosonde flights are used to robustly detect systematic differences between the instruments (e.g. Luers and Eskridge, 1998;Steinbrecht et al, 2008;Kobayashi et al, 2012;Jensen et al, 2016). Results presented in Steinbrecht et al (2008) indicated that temperature biases often increase significantly with increasing altitude, particularly in the lower stratosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Results presented in Steinbrecht et al (2008) indicated that temperature biases often increase significantly with increasing altitude, particularly in the lower stratosphere. Instrument biases are also influenced by clouds as shown in Jensen et al (2016) who found systematic differences in temperature measurements greater than 2K between the Vaisala RS92 and RS41 radiosonde when exiting cloud layers. This large difference in temperature measurements between the two radiosondes was attributed to the wet-bulb effect, where the 25 temperature sensor gets wet while passing through a cloud layer and is subject to evaporative cooling after entering dryer parts of the atmosphere.…”
mentioning
confidence: 99%
“…Typically, intercomparisons of measurements from dual or quadruple (two of each instrument-type) radiosonde flights are used to robustly detect systematic differences between 20 the instruments (e.g. Luers and Eskridge, 1998;Steinbrecht et al, 2008;Jensen et al, 2016). Results presented in Steinbrecht et al (2008) indicated that temperature biases often increase significantly with increasing altitude, particularly in the lower stratosphere.…”
mentioning
confidence: 99%
See 1 more Smart Citation